Mutagenic potential of lettuce grown from irradiated seeds - Franco, Caio Haddad [UNESP]; Santos, Valter Henrique Marinho dos [UNESP]; Silva, Luciana Pereira [UNESP]; Arthur, Valter; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2015)
Agriculture has benefited from the use of radiation techniques, which provide plant varieties with distinguishing characteristics, such as higher productivity, precocity and greater resistance to disease, pests and harsh weather conditions. Therefore, this study aimed to analyze the mutagenicity of greenhouse-developed Lactuca sativa originated from gamma-irradiated seeds. The seeds were irradiated at doses of 25, 50, 75, 150 and 300 Gy and after done ethanol extract this seeds in three concentrations (50, 100 and 200 mg of extract/ml of water). Tests were performed based on biological assays with Allium cepa. The extracts of plants from seeds with higher levels of irradiation showed greater mitodepressive effect and number of aberrant cells may be correlated with the increase in free radicals produced by the radiation. Based on these results, we conclude that although irradiation is a useful technique in plant breeding programs, it is extremely important to evaluate the radiation dose, which guarantees the well-being of the final consumer.
Keywords: Seeds irradiation; Lactuca sativa L.; Allium cepa test